Oestradiol Treatment Counteracts the Effect of Fructose-Rich Diet on Matrix Metalloproteinase 9 Expression and NFκB Activation - Bundalo, M; Zivkovic, M; Culafic, T; Stojiljkovic, M; Koricanac, G; Stankovic, A (Folia biologica, 2015)
Fructose-rich diet induces metabolic changes similar to those observed in metabolic syndrome. Among other matrix metalloproteinases, MMP-9 has an important role in adverse cardiac remodelling and might have a role in the development of cardiovascular disorders associated with metabolic syndrome. The changes of MMP-9 expression could be mediated via the NFκB pathway. In this study we investigated the effect of fructose-rich diet on MMP-9 expression in the heart of male and female rats, along with the effect of fructose-rich diet and oestradiol on MMP-9 expression in ovariectomized females. We further assessed the effect of fructose-rich diet and oestradiol on NFκB activation, measured as the level of p65 phosphorylation at Ser 276. The results showed that the diet regime did not affect the heart mass. Higher MMP-9 gene expression was found in cardiac tissue of male rats fed the fructose-rich diet than in females on the same diet regime. In ovariectomized females, fructose-rich diet upregulated MMP-9 protein and mRNA expression in the heart, as well as phosphorylation of the p65 subunit of NFκB at Ser 276. Oestradiol replacement therapy reverted these changes in the heart of ovariectomized females. This study has shown that oestradiol could revert the early molecular changes in MMP-9 expression induced by fructose-rich diet that occurred before cardiac hypertrophy development by decreasing phosphorylation of the NFκB p65 subunit at Ser 276.
Keywords: Animals; Gene Expression Regulation, Enzymologic; Female; regulace genové exprese enzymů; Rats, Wistar; Fructose; Phosphoserine; ženské pohlaví; Organ Size; Ovariectomy; messenger RNA; Matrix Metalloproteinase 9; fruktosa; transkripční faktor RelA; dieta; RNA, Messenger; tělesná hmotnost; velikost orgánu; fosforylace; matrixová metaloproteinasa 9; Diet; Male; Transcription Factor RelA; Body Weight; NF-kappa B; zvířata; mužské pohlaví; ovarektomie; fosfoserin; Estradiol; Myocardium; myokard; Phosphorylation; estradiol; potkani Wistar